Nutritional composition, physico-chemical, and sensory characteristics of rolled oats snack bars formulated with green banana (musa acuminata x balbisiana colla cv.awak) flour - Norhidayah Che Adri
Snack bar, a popular and convenient ready-to-eat snack, is continued to grow in sales. Most of the snack bars sold in the market are of high sugar and glycaemic index which cause powerful spikes in blood sugar for energy supplied. This subsequently leads to increasing risk of obesity, type-2 diabetes, cardiovascular disease, and other diseases associated with ageing. Therefore, regular intake of fruits is very important for maintaining human health by protecting from several life-style related diseases. However, one of the constraints in increasing fruits consumption is time required to prepare them. Thus, fruits transformed into more convenient ready-to-eat food such as snack bar would be an ideal food format to eat as part of a meal. This study aims to determine the nutritional composition and physico-chemical properties of rolled oats based-snack bars made with different levels of green banana flour, investigate the estimated glycaemic index of rolled oats-based-snack bars made with different levels of green banana flour, and evaluate the sensory characteristics of rolled oats-bas ed snack bars made with different levels of green banana flour. Green banana flour (GBF) was incorporated in proportions of 5, 10, 15, and 20% on rolled oats basis in snack bar to prepare snack bar and labelled as SBF5, SBFIO, SBFI5, and SBF20, respectively. Snack bar without GBF served as control. The nutritional composition, chemical properties, and physical properties of the snack bars were assessed according to the standard methods. The estimated glycaemic index of all the snack bars was performed by in vitro assay. All of the snack bars were evaluated for sensory characteristics by 7- hedonic scale. The addition of GBF significantly decreased the moisture and crude protein contents, but significantly increased the ash, crude fiber, crude fat, and carbohydrate contents, as well as the calorie values. The vitamin C, pH, total soluble solid, and total sugars contents were found to increase significantly, while the water activity decrease significantly, with increasing substitution level ofGBF for rolled oats. Snack bars containing GBF had significantly higher level of insoluble dieteary fibre, soluble dietary fibre, total dietary fibre, total starch, and resistant starch than that of control. Higher substitution level of GBF in snack bars had significantly increased the amount of total phenolic content, total flavonoid content, and antioxidant values than that of control. Texture profile analysis indicated that all the samples were significantly different from each other in terms of hardness and cohesiveness. The addition of GBF significantly reduced the lightness (L *) and increased the yellowness (b*) of snack bars. A slow starch hydrolysis rate was recorded with a subsequent reduction of hydrolysis index and estimated glycaemic index in snack bars containing GBF. Sensory evaluation indicated that snack bar containing 15% (w/w) of GBF (i.e., SBFI5) had the highest overall acceptability (score> 6). The findings from this study showed that GBF has the potential to be incorporated into snack bars to improve its' properties, especially in nutrition, functional, and sensory aspects. As this is a novel snack bar developed with low estimated glycaemic index value, it is expected to benefit consumers, especially those following weight management programme, as well as for diabetic patients.